2021
DOI: 10.3390/jcm10112316
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Non-Tumoral Portal Vein Thrombosis Management in Cirrhotic Patients: TIPS Versus Anticoagulation Versus No Treatment

Abstract: Background: There is a lack of consensus in optimal management of portal vein thrombosis (PVT) in patients with cirrhosis. The purpose of this study is to compare the safety and thrombosis burden change for cirrhotic patients with non-tumoral PVT managed by transjugular intrahepatic portosystemic shunt (TIPS) only, anticoagulation only, or no treatment. Methods: This single-center retrospective study evaluated 52 patients with cirrhosis and non-tumoral PVT managed by TIPS only (14), anticoagulation only (11), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 21 publications
(38 reference statements)
0
22
0
Order By: Relevance
“…In a recent study by Zhan et al, TIPS improved thrombus burden in 72% of patients while only 27 and 10% of anticoagulated and untreated patients, respectively, demonstrated improvement. 27 In a recent meta-analysis by Valentin et al, the authors reported 84.4% complete and partial recanalization and 74% complete recanalization rates with TIPS. 30 Sun et al demonstrated the efficacy of TIPS in controlling the portal vein pressure and rebleeding rates in patients with chronic PVT ( Table 5 ).…”
Section: Portal Vein Thrombosismentioning
confidence: 97%
See 1 more Smart Citation
“…In a recent study by Zhan et al, TIPS improved thrombus burden in 72% of patients while only 27 and 10% of anticoagulated and untreated patients, respectively, demonstrated improvement. 27 In a recent meta-analysis by Valentin et al, the authors reported 84.4% complete and partial recanalization and 74% complete recanalization rates with TIPS. 30 Sun et al demonstrated the efficacy of TIPS in controlling the portal vein pressure and rebleeding rates in patients with chronic PVT ( Table 5 ).…”
Section: Portal Vein Thrombosismentioning
confidence: 97%
“…25 In addition, around 36% recurrence rate has been reported after the discontinuation of anticoagulation. 27 These limitations of anticoagulation are the determinants that favor TIPS in clinical practice.…”
Section: Portal Vein Thrombosismentioning
confidence: 99%
“…The rates of major complications were 10% [ 156 , 157 ]. When compared to anticoagulation, TIPS has a higher effectiveness in terms of portal vein recanalization [ 158 , 159 ]. Regarding portal-hypertension-related complications, two randomized controlled trials have evaluated the effectiveness of TIPS in comparison to standard therapy (endoscopic band ligation + propranolol + anticoagulation) for the prevention of variceal rebleeding in cirrhotic patients with PVT.…”
Section: Treatmentmentioning
confidence: 99%
“…PVT is a frequent and serious complication of liver cirrhosis (LC), particularly in its advanced stages. Namely, the prevalence of PVT range between 0.6% and 28% in patients with cirrhosis 2 . Remarkably, most patients are asymptomatic at the time of PVT diagnosis 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the prevalence of PVT range between 0.6% and 28% in patients with cirrhosis. 2 Remarkably, most patients are asymptomatic at the time of PVT diagnosis. 3 However, the 2‐year survival rate of patients with PVT is reduced by 55% compared with patients without PVT due to hepatic dysfunction.…”
Section: Introductionmentioning
confidence: 99%